การสังเคราะห์วงจรขยายในโหมดกระแสด้วย VDTA เพียงตัวเดียว A Synthesis Current-mode Amplifier Employing Single VDTA - ลีกุลธร, พุทธาวุฒิ; วิชิโต, ชิติสรรค์; ศรีสกุลเตียว, สมชาย (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2016)
บทคัดย่อ บทความวิจัยนี้นำเสนอการสังเคราะห์วงจรขยายในโหมดกระแสด้วย VDTA เพียงตัวเดียว ที่มีลักษณะเด่น คือใช้อุปกรณ์แอกทีฟ VDTA เพียงตัวเดียวปราศจากอุปกรณ์พาสซีฟ สามารถปรับอัตราขยายได้ ด้วยวิธีทางอิเล็กทรอนิกส์ มีผลกระทบกับอุณหภูมิเพียงเล็กน้อยที่ 27 - 100oC ผลการจำลองด้วย PSpice พบว่าวงจรสามารถทำงานได้สอดคล้องตามที่คาดการณ์ไว้ในทฤษฎี มีผลตอบสนองทางความถี่ เกือบ 100 MHz มีอัตราการสิ้นเปลืองพลังงาน 0.58 mW ที่แหล่งจ่าย 1.5 โวลต์ อีกทั้งยังสามารถ ประยุกต์ใช้งานในการสื่อสารข้อมูลได้อีกด้วย Abstract This article describes a synthesis current-mode amplifier employing single VDTA (Voltage Differencing Transconductance Amplifier). Their features are following: using VDTA only without any passive elements, electronically controllable, and non-effect in low temperature at 27 - 100oC. The simulation results obtained from PSpice are accordance with the theoretical predictions. The proposed circuit has frequency responds of more 100 MHz and power consumption 0.58 mW at 1.5 V supply voltage. It can be application to the data communication.